2011
DOI: 10.1002/app.35099
|View full text |Cite
|
Sign up to set email alerts
|

SEC‐MALS study of dynamic structuring of natural rubber: Comparative study of two Hevea brasiliensis genotypes

Abstract: ABSTRACT:The dynamic structuring of natural rubber (NR) was studied selecting two specific Hevea brasiliensis genotypes (RRIM600 and PB235) to prepare model samples. The mesostructure (macromolecular structure þ aggregates or gel) of NR samples was studied by SEC-MALS. The NR samples were analyzed after (i) slow structuring (18 months' storage at room temperature) and (ii) fast structuring (stored for 24 h on P 2 O 5 at 60 C). This study showed that the macromolecular structure, especially M n , and the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…A minor fraction of minerals was also found in the soluble fractions (Figure ). Given that the microgel of NR samples can account for more than 30% w/w, it is clear that the microaggregates present in NR are not composed of minerals only, which account for 0.2% of the total weight of NR . However, the mineral aggregates observed in the soluble fractions could be associated with the microgel phase of NR, according to previous results .…”
Section: Resultssupporting
confidence: 70%
“…A minor fraction of minerals was also found in the soluble fractions (Figure ). Given that the microgel of NR samples can account for more than 30% w/w, it is clear that the microaggregates present in NR are not composed of minerals only, which account for 0.2% of the total weight of NR . However, the mineral aggregates observed in the soluble fractions could be associated with the microgel phase of NR, according to previous results .…”
Section: Resultssupporting
confidence: 70%
“…The gel structure, is influenced by non-isoprene components, especially the protein materials, and more proteins are found in the gel phase compared to the sol phase [89]. Proteins are thought to be linked at the u-terminal (the trans-initiator group) of the polyisoprene, but the mechanism of interaction is still elusive as lipids could also alternatively be present in the core of the microgel [88,90]. Additionally, it is assumed that the dimethylallyl group is modified either enzymatically or chemically after polymerization [77,91].…”
Section: Role In Rubber Biosynthesis and Branchingmentioning
confidence: 98%
“…Mg þþ ) [82,87]. A "bifunctional polyisoprene" model is therefore expected, allowing a dynamic structuration of natural rubber, including micro and macrogels (unsoluble rubber phase after solubilizing in solvent) [88] (Fig. 6).…”
Section: Role In Rubber Biosynthesis and Branchingmentioning
confidence: 99%
“…After dissolution, macrogel is eliminated by centrifugation. Filtration of the soluble fraction can then be used to quantify the microgel either directly by weighing the recovered microgel [25], or indirectly using SEC-MALS (size exclusion chromatography, multiple angle light scattering) analyses [12,26]. Several studies showed that proteins are concentrated in the macrogel of NR [27][28][29].…”
Section: Introductionmentioning
confidence: 99%